PAKAN DAN KEBIASAAN MAKAN IKAN KEMBUNG LELAKI (Rastreliger canagurta) DI PERAIRAN SEKITAR SORONG - Siti Asma; Intanurfemi B Hismayasari (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2018)
This study aims are to identify the type of food mackerel fish and classifying mackerel by their food habits is nearby of Sorong Sea. This Study was conducted from May 2011 to December 2011. Samples were analized at the Fisheries Laboratory of Sorong Fisheries Academy, West Papua. Fish samples obtained from thw catch of fisherman that landed on fish auction place Jembatan puri and Boswesen. The samples used are 372 fishes consisted of 215 males and 157 females. Fish samples analyzed descriptively based on the relationship of total length and body weight of fish, condition factors and food habits. Equation total length relationship with the weight of the fish indicated that the value of the regression coefficient (b) is 2.005 and R2=0,924 and r=0961 indicates that there is a relationship between body length and body weight. Observations on the value of the average condition factors ranged between 0.9031-1.1574. The observation of the gastric contents is known that the greatest composition were from the genus Rhizosolenia = 67.16 % followed by Paracalanus,Acartia,anchovy and fish scales respectively – each sequence was 24.72 %, 15.5 % and 10.33%. The research concluded that the Mackerel Fish (Rastreliger canagurta) is an omnivorous fish based on food habits in its gastric contents were plankton (phytoplankton and zooplankton), fragments of animal and plant.